2016
DOI: 10.1128/mbio.01847-16
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Bacteria Attenuate Klebsiella pneumoniae Burden in Rat Lungs

Abstract: Bdellovibrio bacteriovorus and Micavibrio aeruginosavorus are predatory bacteria that naturally—and obligately—prey on other Gram-negative bacteria, and their use has been proposed as a potential new approach to control microbial infection. The ability of predatory bacteria to prey on Gram-negative human pathogens in vitro is well documented; however, the in vivo safety and efficacy of predatory bacteria have yet to be fully assessed. In this study, we examined whether predatory bacteria can reduce bacterial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 36 publications
6
87
0
6
Order By: Relevance
“…Recently, we demonstrated the ability of predatory bacteria to attenuate bacterial burden in vivo within the lungs of rats 19 . In this study, we extend this approach to determine if predatory bacteria can reduce bacterial burden introduced directly into the rat vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated the ability of predatory bacteria to attenuate bacterial burden in vivo within the lungs of rats 19 . In this study, we extend this approach to determine if predatory bacteria can reduce bacterial burden introduced directly into the rat vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Although their association with the human body is not firmly established, their ability to prey on pathogenic gramnegative bacteria and the low immune responses they generate (Monnappa et al, 2016;Shatzkes, Singleton, et al, 2017) have made them a focus of interest for the development of novel antimicrobial strategies Shatzkes, Connell, et al, 2017). Their application in vivo shows they can curb certain infections in mucus-lined habitats (Shatzkes et al, 2016;Willis et al, 2016;De Dios Caballero et al, 2017), further increasing the need to understand their behaviour under body cavity-relevant conditions. We thus explored the behaviour of three different BALOs under various viscosities and temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that constructed habitats largely change BALO predatory dynamics (Hol et al, 2016;Dattner et al, 2017), but our results suggest that the macro-molecular environment also alters predator-prey interactions. This is relevant to the applications of BALOs against pathogenic bacteria as BALOs have been tested as possible treatments for lung infections, whereby they should be active in mucus, and in plasma (Shatzkes et al, 2016;Baker et al, 2017), two habitats totally different in terms of spatial structure as well as in macromolecular composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the increment of Bdellovibrionaceae occurred only in the AB++ treatment. This family is notorious for preying on other bacteria, and organisms of this family have often been suggested as potential natural antimicrobials because of their preference for gram‐negative antibiotic‐resistant bacteria (Shatzkes et al, ; Sockett & Lambert, ). Our results can be considered an indirect confirmation of those findings, as Bdellovibrionaceae have an ecological advantage in treatment AB++, where they seem to find their ideal growth conditions.…”
Section: Discussionmentioning
confidence: 99%